2014
DOI: 10.1155/2014/340765
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship betweenH. pyloriInfection and Osteoporosis in Japan

Abstract: Background and Objective. H. pylori infection causes a chronic inflammation in the gastric mucosa. However, this local inflammation may result in extra-digestive conditions. Our aim is to investigate the relationship between H. pylori infection and osteoporosis in Japan. Methods. This cross-sectional study was conducted among outpatients at the Juntendo University Hospital between 2008 and 2014. Participants for patient profile, H. pylori infection status, comorbidity, internal medical therapies, lumbar dual-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Four studies reported a positive association between H . pylori infection and osteoporosis [22,2729]. Figura et al [22] reported that male patients infected by CagA protein–producing H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported a positive association between H . pylori infection and osteoporosis [22,2729]. Figura et al [22] reported that male patients infected by CagA protein–producing H .…”
Section: Discussionmentioning
confidence: 99%
“…pylori strains had higher values of a urinary bone fracture biomarker. Two hospital-based studies from Japan by Asaoka et al [27,29] and 1 from Taiwan by Lin et al [28] reported an association between H . pylori infection and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study similarly divided subjects into 2 groups at age 50, and a significant relationship was noted between age (50 years or older) and osteopenia [19]. Causes may include reduced osteoblast function and calcium absorption due to aging [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis using 5 studies [15,18,20,21,44] from Asian countries demonstrated that H. pylori infection does not seem to be an important factor related to osteopenia [45]. However, some previous studies showed a relationship between H. pylori infection and osteoporosis [16,17,18,19,20,21]. In most of these studies, H. pylori infection was diagnosed by serum anti- H. pylori IgG antibody titers or histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation